الضمان وتطبيقاته المعاصرة (خطاب الضمان نموذجا) - مــحـــرز, دو (University of Eloued جامعة الوادي, 2019)
"جاءت هذه الدّراسة بعنوان: ""القياس على الرّخص الشّرعيّة وأثره على الفروع الفقهيّة"" لتبحث في حكم القياس على الرّخصة، انطلاقا من إشكالية رئيسة مضمونها: إذا كان كلّ حكم شرعيّ يمكن تعليله يجري فيه القياس، فهل يتحقّق ذلك في الرّخص عند الاتّفاق في العلّة وتشابه الأعذار؟ وما ضابط ذلك ؟ وقد استدعت الإجابة عن هذا السؤال المحوري أسئلة أخرى رسمت مجتمعة خطّة هذا العمل الذي قام على فصلين سبقتهما مقدمة وتلتهما خاتمة ؛ وقد عُنيت في الفصل الأوّل منهما بتحديد مفهوم القياس والرّخص الشّرعيّة، بينما اختصّ الفصل الثّاني بتوضيح خلاف العلماء في القياس على الرّخص وأثره على الفروع الفقهيّة. وتوصّلت في نهاية دراستي إلى نتائج أهمّها: جواز القياس على الرّخص إذا علمنا العلّة التي من أجلها شرعت الرّخصة، وتحققنا من وجودها في الفرع المقيس عليه مع استكمال شروط القياس، وفي هذا -ربط بين الأحكام الشّرعية ومقاصد الشّريعة برفع الحرج عن المكلّفين وتحقيق مصالحهم. " "Abstract This study is devoted to the subject of Guarantee and Its Contemporary Applications and used The Letter of Guarantee as a study model. Guarantee is one of the contracts initiated by the Muslim as a way of easement and benevolence to promote the social solidarity among Muslims. In view of the evolution of economic life, banks have tended to adopt this contract in exchange for a replacement, because of the confidence it provides between the dealers and the stability of economic transactions. It has created many of its derivative banking products, most notably the letter of guarantee that is now a condition in many contracts and tenders. So, what is guarantee in Islamic jurisprudence? And what is the letter of guarantee? The study concluded that there is an unanimity of the scholars that it is impermissible to take a compensation instead of the financial guarantee, because it is a contract that reverts to a loan, which applies to the non-covered letter of guarantee. Whereas, for the covered one, the bank is the agent of the debtor in the performance of his debt, which allows him to obtain a commission in exchange for this service. Accordingly, Islamic banks are called upon to find legitimate alternatives to compensated guarantee, hopefully to be prevailed by investment formulas in order to contribute positively to national economies."
مذكرة ماستر تخصص معاملات مالية معاصرة
Keywords: الضمان، خطاب الضمان، خطاب الضمان غير المغطى، خطاب الضمان المغطى; Guarantee ، Letter of Guarantee، non-covered letter of guarantee، covered letter of guarantee